Approaching Existential Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2003)
An informal presentation of a personal approach to psychotherapy, based on the author's learnings through the teaching and supervision of Dr Hans W Cohn, as well as integration of principles from other practitioners. The paper consists of introductory sections, personal reminiscences, discussion and comments, followed by themes drawn from supervision.